2018
DOI: 10.1177/0032329218789886
|View full text |Cite
|
Sign up to set email alerts
|

Legislature by Lot: Envisioning Sortition within a Bicameral System

Abstract: In this article, we review the intrinsic democratic flaws in electoral representation, lay out a set of principles that should guide the construction of a sortition chamber, and argue for the virtue of a bicameral system that combines sortition and elections. We show how sortition could prove inclusive, give citizens greater control of the political agenda, and make their participation more deliberative and influential. We consider various design challenges, such as the sampling method, legislative training, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 9 publications
0
72
0
4
Order By: Relevance
“…Prerogatives Finally, and perhaps most importantly when it comes to the broader impact of DMPs on contemporary democracies, it is important to consider what actual political role has this form of democratic innovation. Do DMPs remain pure advisory bodies or do we observe some instances of DMPs that have a stronger role, perhaps going in the direction of mini-publics as second chamber of parliament as discussed, for example, by Gastil and Wright ( 2019 )? Moreover, the literature has shown that the lack of clear and decisive prerogatives for DMPs is one of the reasons why many citizens refuse to participate in such forms of democratic innovation (Jacquet 2017 ).…”
Section: Presentation Of the Datasetmentioning
confidence: 99%
“…Prerogatives Finally, and perhaps most importantly when it comes to the broader impact of DMPs on contemporary democracies, it is important to consider what actual political role has this form of democratic innovation. Do DMPs remain pure advisory bodies or do we observe some instances of DMPs that have a stronger role, perhaps going in the direction of mini-publics as second chamber of parliament as discussed, for example, by Gastil and Wright ( 2019 )? Moreover, the literature has shown that the lack of clear and decisive prerogatives for DMPs is one of the reasons why many citizens refuse to participate in such forms of democratic innovation (Jacquet 2017 ).…”
Section: Presentation Of the Datasetmentioning
confidence: 99%
“…One of the cornerstones of deliberative democracy is participant inclusivity and representativeness. The method of 'sortition' , or random selection, or selection by lot, has been proposed as ideal to ensure representativeness of the broad population involved, with stratified sampling to ensure the group selected mirrors the populations' demographics [61]. However, other methods may be used to ensure inclusion, depending on the nature of the deliberative forum, and such that the broadest spectrum of the population is elicited to participate [62].…”
Section: Deliberative Democracymentioning
confidence: 99%
“…Once selected, committee membership would be allocated on the basis of length of service and preference: "Current committee members who remain in the assembly could retain their most preferred committee assignments, then enter into a lottery with the rest of the selectees, each of whom would have ranked their preferences like students signing up for courses." 10 To our knowledge, such long terms of continual service and the freedom of members to choose areas of work according to preference and length of service are unprecedented for a sortition body. In ancient Athens, where the Council, courts, and boards selected members randomly by lot, there was relatively rapid rotation of tasks and offices.…”
Section: The Case For Rotationmentioning
confidence: 99%
“…Gastil and Wright stress that "a place for traditional caucusing should remain," or "members could organize themselves into a larger number of more cohesive groups of like-minded legislators, who share common values and priorities." 12 Either of these-and especially their combination-threatens to move the legislature away from the deliberative ideal of autonomous agents swayed by the force of the better argument and toward a more structured partisanship that works across issue areas.…”
Section: The Case For Rotationmentioning
confidence: 99%